2011
DOI: 10.1128/iai.00309-10
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Experimental Cutaneous Leishmaniasis by Leishmania Molecules Is Dependent on Interleukin-4, Serine Protease/Esterase Activity, and Parasite and Host Genetic Backgrounds

Abstract: Most inbred strains of mice, like the BALB/c strain, are susceptible to Leishmania amazonensis infections and resistant to Leishmania braziliensis infections. This parasite-related difference could result from the activity of an L. amazonensis-specific virulence factor. In agreement with this hypothesis, it is shown here that the intravenous injection of BALB/c mice with L. amazonensis amastigote extract (LaE) but not the L. braziliensis extract confers susceptibility to L. braziliensis infection. This effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 32 publications
5
21
0
Order By: Relevance
“…A similar effect was observed in the pre-vaccination treatment when using whole L. amazonensis antigen from amastigotes named L. amazonensis amastigote extract (LaE) followed by a challenge with L. braziliensis [34]. The increase of susceptibility of infection in immunized mice was dependent on the maintenance of serine protease activity.…”
Section: Whole L Amazonensis Antigens From Promastigotes (Laag) and mentioning
confidence: 48%
See 2 more Smart Citations
“…A similar effect was observed in the pre-vaccination treatment when using whole L. amazonensis antigen from amastigotes named L. amazonensis amastigote extract (LaE) followed by a challenge with L. braziliensis [34]. The increase of susceptibility of infection in immunized mice was dependent on the maintenance of serine protease activity.…”
Section: Whole L Amazonensis Antigens From Promastigotes (Laag) and mentioning
confidence: 48%
“…This suggested that LaSP-Sol induced an immune response with a Th2 profile and/or activation of regulatory T cells. However, a comparison between effects using LaSP-Sol to LaAg in BALB/c mice immunized intramuscularly showed a similar profile in lesions and parasite burden compared to non-vaccinated mice [34].…”
Section: Soluble Serine Proteases From Leishmania Amazonensis (Lasp-sol)mentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the humoral immune response, only F1-immunized animals exhibited an increase in the production of IgG2a compared to non-immunized mice, which could have a direct association with high IFN-c levels [34]. F5-immunized mice exhibited an increase in IgG1 isotype, which can be associated directly with high levels of IL-4 and parasitism in lymph nodes [43]. Therefore, immunization with F1 confers protection on skin and popliteal lymph nodes, associated with an increasing Th1 immune response; however, F5-immunized animals could limit parasite infection of the skin and were associated with a mixed immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that some secreted factors from L. major possess immunosuppressive properties, could dampen lymphoproliferative capabilities and skew T cell polarization toward a susceptible Th2 phenotype (Tabatabaee, Abolhassani, Mahdavi, Nahrevanian, & Azadmanesh, 2011). Similarly, extracts of L. amazonensis , a causative agent of CL in the New World, promote a Th2 type immune response in the host, thereby enhancing infection (Silva et al, 2011). …”
Section: Mechanisms Of Immune Evasionmentioning
confidence: 99%